Polanyi and Hayek on Freedom, the State, and Economics - Filip, Birsen (International Journal of Political Economy, 2012)
This paper examines the relationship that prevails between the state, economics, and freedom according to the works of Friedrich Hayek and Karl Polanyi. Hayek, who was one of the most important contributors to the development of the modern market economy and liberalism, formulated a concept of freedom that includes economic and negative freedom as significant components; his objective was to demonstrate the superiority of liberal capitalist societies over all other forms of organizing a society in terms of achieving freedom. Meanwhile, Polanyi, who confronted all forms of totalitarian regimes and argued that a "self-regulating market … was a utopian project," formulated a concept of freedom that rejected the self-regulating mechanism of the market economy as a component of freedom; he supported regulated markets and included moral, ethical, and social values among the key components required for the realization of freedom. This paper shows that Hayek failed to foresee the destructive social consequences and dehumanizing aspects of modern market capitalism, and promoted the free market economy as a guardian of freedom primarily for its instrumental value. Conversely, Polanyi was able to anticipate the modern market economy's potential to engender disastrous consequences for the whole of humanity and provided an honest and objective analysis of the modern market system that is indispensable for understanding the dilemmas, issues, and contradictions of economic globalization.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; capitalism; economics; globalization; modern market economy; negative freedom; open society; political philosophy; positive freedom

The Belief in Economic Determinism, Neoliberalism, and the Significance of Polanyi's Contribution in the Twenty-First Century - Thomasberger, Claus (International Journal of Political Economy, 2012)
How can we explain why Karl Polanyi's book The Great Transformation is more relevant today than ever before? The central thesis of the paper is that Polanyi's analysis is groundbreaking because it goes far beyond the interpretation of the civilization of the nineteenth century. By focusing on the "belief of economic determinism," Polanyi challenges the juxtaposition of being and thinking, of material life-process and consciousness. He rejects the assumption that society encompasses a world of objective facts independent of theoretical beliefs and visions. Polanyi's work is of utmost importance today because by anticipating a change in approach such as the liberal authors made, from the opposite point of view, during the interwar period, he offers the key not only to the analysis of the market mechanism, but also to a critical understanding of neoliberalism.
Keywords: Austrian school; Austrian school of economics; Great Transformation, The (Book); Keynesian economics; Marxist philosophy; POLANYI, Karl, 1886-1964; belief & doubt - social aspects; central economic planning - social aspects; double movement; economic determinism; economic history - 19th century; economic planning; economic theory; fictitious commodities; free enterprise - social aspects; history of economics - 20th century; human behavior - economic aspects; laissez-faire; neoliberalism; neoliberalism - social aspects; self-fulfilling prophecy; socioeconomics; utopias - economic aspects

'Planning for Freedom': Hayekian and Polanyian Policies in Latin America - Valderrama, Paula (International Journal of Political Economy, 2012)
In the first part of the paper, the concepts of "planning for freedom" by Friedrich Hayek and Karl Polanyi are compared. Hayek rejects "central planning" and also all kinds of "planning for specific aims," but he defends the principle of "planning for competition" as the main condition of a free society. This principle includes the provision of a pertinent institutional framework and state intervention to create markets in spheres of society previously ruled by nonmarket principles. Polanyi agrees that "planning" is necessary in order to achieve freedom in a complex society, but he criticizes the liberal understanding of freedom as a vain "illusion" and considers the principle of "planning for competition" a political ideal that endangers the cohesion of societies. The starting point of Polanyi's argumentation is Karl Marx's theory of reification, but he goes beyond this, complementing it with the concept of "social freedom" based on knowledge and responsibility. Considering the Latin American experience in recent decades, the paper compares Hayekian and Polanyian concepts of "planning for freedom" in their real political and social dimensions.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Latin America; capitalist systems: planning, coordination, and reform; formal and informal sectors; freedom; history of economic thought: individuals; institutional arrangements; planning models; planning policy; political processes: rent-seeking, lobbying, elections, legislatures, and voting behavior; shadow economy